2014
DOI: 10.7860/jcdr/2014/7646.4296
|View full text |Cite
|
Sign up to set email alerts
|

Primary Fibrosarcoma of Male Breast: A Rare Entity

Abstract: Primary fibrosarcoma of the breast is a very rare tumor. However, amongst the Primary Breast Sarcoma (PBS), it is the most common subtype. We present a case of 28-year-old male with lump in right breast of 7 year duration. The unilateral multinodular mass showed well circumscribed but unencapsulated tumor composed of interlacing fascicles of spindle shaped cells with minimal atypia. Immunohistochemistry revealed positivity for vimentin in the tumor cells. Differential diagnoses and review of literature is disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It is of major interest to identify the clinical characters and the prognosis factors for the PBS and MPT. Sarcoma of the breast is mainly present in women, male patients usually representing <5% (9,23). Mean age ranges from 47 to 52 years, and mean size of tumor ranges from 5.5-5.7 cm (1,9,17).…”
Section: Discussionmentioning
confidence: 99%
“…It is of major interest to identify the clinical characters and the prognosis factors for the PBS and MPT. Sarcoma of the breast is mainly present in women, male patients usually representing <5% (9,23). Mean age ranges from 47 to 52 years, and mean size of tumor ranges from 5.5-5.7 cm (1,9,17).…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosarcoma is also a malignant tumor, which is derived from fibrous connective tissue. Fibrosarcoma was usually found in males with poor prognosis for metastasis, especially to breast [ 28 31 ]. Chemotherapy or radiotherapy has poor effects on treating fibrosarcoma, and surgical resection or amputation is considered as the primary treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The rarity of lobular carcinoma in males in comparison with females is due to the lack of terminal lobules in male breasts. Although rare, still infinitesimal cases of primary breast sarcoma are found in male breasts [19]. A few cases of basal cell and Merkel cell carcinoma of male breasts were also reported [20,21].…”
Section: Histopathological Classificationmentioning
confidence: 99%
“…A few retrospective studies on MBC have been reported from India (Tab. 2 [1,12,15,19,28,[42][43][44][45][46][47][48]). These studies are important to understand the current situation of MBC in different parts of India.…”
Section: Indian Setting Of Mbcmentioning
confidence: 99%